Character strengths and well-being across the life span: data from a representative sample of German-speaking adults living in Switzerland - Martínez-Martí, María L.; Ruch, Willibald (Frontiers in Psychology, 2014)
Character strengths are positive, morally valued traits of personality. This study aims at assessing the relationship between character strengths and subjective well-being (i.e., life satisfaction, positive and negative affect) in a representative sample of German-speaking adults living in Switzerland (N = 945). We further test whether this relationship is consistent at different stages in life. Results showed that hope, zest, love, social intelligence and perseverance yielded the highest positive correlations with life satisfaction. Hope, zest, humor, gratitude and love presented the highest positive correlations with positive affect. Hope, humor, zest, honesty, and open-mindedness had the highest negative correlations with negative affect. When examining the relationship between strengths and well-being across age groups, in general, hope, zest and humor consistently yielded the highest correlations with well-being. Additionally, in the 27-36 years group, strengths that promote commitment and affiliation (i.e., kindness and honesty) were among the first five positions in the ranking of the relationship between strengths and well-being. In the 37-46 years group, in addition to hope, zest and humor, strengths that promote the maintenance of areas such as family and work (i.e., love, leadership) were among the first five positions in the ranking. Finally, in the 47-57 years group, in addition to hope, zest and humor, strengths that facilitate integration and a vital involvement with the environment (i.e., gratitude, love of learning) were among the first five positions in the ranking. This study partially supports previous findings with less representative samples on the association between character strengths and well-being, and sheds light on the relative importance of some strengths over others for well-being across the life span.